The cement consumption detail of BRAC University new campus project from October 2018 to July 2019 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the cement consumption detail from October 2018 to July 2019 of BRAC University new campus project.